Opportunism and reciprocity in economic behaviour: “Public Goods” game results - case study of Ukraine - Merkulova, Tamara Viktorivna; Bitkova, Tatyana Viktorivna (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
The article presents detailed analysis of the outcomes of Public Goods game, which was held in Ukraine in order to study the behavioural features, influencing cooperation intensity and efficiency. Experimental results agree with those of earlier research and may serve as an argument for the following conclusions. Combination of readiness for coopera-tion and inclination to punishment may lead to cooperation establishment and its stabilization, but doesn’t allow to use its potential and get a substantial effect. Considering taxation and tax policy, experimental results allow us to doubt the fact, that loosening of control and punishment is always leading to widening of tax evasion. Opportunistic behaviour of taxpayers on the post soviet area to a considerable extent is explained by the violation of the parity in the exchange of paid taxes for public goods. The results of the research were reported on the The Fifth ISBEE World Congress (Warsaw, 2012).